The Roles of Suspension-Feeding and Flux-Feeding Zooplankton as Gatekeepers of Particle Flux Into the Mesopelagic Ocean in the Northeast Pacific - Stukel, Michael R.; Ohman, Mark D.; Kelly, Thomas B.; Biard, Tristan (Frontiers in Marine Science, 2019)
Zooplankton are important consumers of sinking particles in the ocean’s twilight zone. However, the impact of different taxa depends on their feeding mode. In contrast to typical suspension-feeding zooplankton, flux-feeding taxa preferentially consume rapidly-sinking particles that would otherwise penetrate into the deep ocean. To quantify the potential impact of two flux-feeding zooplankton taxa (Aulosphaeridae [Rhizaria], and Limacina helicina [euthecosome pteropod]) and the total suspension-feeding zooplankton community, we measured depth-stratified abundances of these organisms during six cruises in the California Current Ecosystem. Using allometric-scaling relationships, we computed the percentage of carbon flux intercepted by flux feeders and suspension feeders. These estimates were compared to direct measurements of carbon flux attenuation made using drifting sediment traps and 238U-234Th disequilibrium. We found that carbon flux attenuation in the shallow twilight zone typically ranged from 500 – 1000 µmol organic C flux remineralized per 10-m vertical depth bin. This equated to approximately 6 – 10% of carbon flux remineralized / 10 m. The two flux-feeding taxa considered in this study could account for a substantial proportion of this flux near the base of the euphotic zone. The mean flux attenuation attributable to Aulosphaeridae was 0.69% / 10 m (median = 0.21%/10 m, interquartile range = 0.04 – 0.81%) at their depth of maximum abundance (~100 m), which would equate to ~ 10% of total flux attenuation in this depth range. The maximum flux attenuation attributable to Aulosphaeridae reached 4.2% / 10 m when these protists were most abundant. L. helicina, meanwhile, could intercept 0.45 – 1.6% of carbon flux / 10 m, which was slightly greater (on average) than the Aulosphaeridae. In contrast, suspension-feeding zooplankton in the mesopelagic (including copepods, euphausiids, appendicularians, and ostracods) had combined clearance rates of 2–81 L m-3 d-1 (mean of 19.6 L m-3 d-1). This implies a substantial impact on slowly sinking particles, but a negligible impact on the presumably rapidly-sinking fecal pellets that comprised the majority of the material collected in sediment traps. Our results highlight the need for a greater research focus on the many taxa that potentially act as flux feeders in the oceanic twilight zone.